Illicit drug and alcohol use and measures of musculoskeletal function and mental health in orthopaedic trauma patients. Issue 2 (27th June 2023) - Spratt, James; Adkins, Zachary; Warda, Danny; Smith, Michele; Bruggers, Jennifer; Weiss, Paul; Becher, Stephen
Abstract: Objectives: The objective of this study was to describe the relationship between positive toxicology screens and measures of preinjury mental health and physical function in an orthopaedic trauma population Design: This was a cross-sectional study. Setting: Urban Level 1 trauma center. Patients: A total of 125 trauma patients gave written consent for this study. Main Outcome Measurements: Questionnaires such as, Patient Health Questionnaire-9, General Anxiety Disorder-7, PCL-5, and Short Musculoskeletal Function Assessment, were used to survey patients after surgical intervention. Results: Patient Health Questionnaire-9 ( P = 0.05) and PCL-5 ( P = 0.04) were not found to have significant differences between positive and negative toxicology screens. Both General Anxiety Disorder-7 ( P = 0.004) and Short Musculoskeletal Function Assessment function ( P = 0.006) were significantly higher in patients with positive toxicology screens. Conclusions: Positive toxicology seems to be associated with preinjury anxiety. Patient reported preinjury function was not adversely affected by the presence of illicit substances or alcohol, nor were levels of post-traumatic stress disorder and depression found to be higher in patients with positive toxicology screens. Level of Evidence: Level IV Cross-Sectional Study.